2014
DOI: 10.1007/s12011-014-0052-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Zinc Oxide Nanoparticles on Growth Performance and Antioxidative Status in Broilers

Abstract: Broilers in four groups were fed a basal diet supplemented with 60 mg/kg zinc oxide (60-ZnO; control), or 20, 60, or 100 mg/kg ZnO nanoparticles (20-, 60-, and 100-nano-ZnO, respectively). Compared with the controls, after 14 days, birds in the 20- and 60-nano-ZnO groups had significantly greater weight gains and better feed conversion ratios. However, the body weight of birds in the 100-nano-ZnO group was dramatically reduced after 28 days. Relative to the control group, the total antioxidant capability (T-AO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
164
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(210 citation statements)
references
References 30 publications
22
164
0
12
Order By: Relevance
“…Because of particle size of nano zinc a faster diffusion through GIT membrane has taken place to reach the cells of the intestinal lining. Our data are in agreement with those obtained by Zhao et al (2014) who stated that after 14 days, birds in the 20 and 60 nano-ZnO groups had significantly greater weight gains and better feed conversion ratios. However, the body weight of birds in the 100-nanoZnO group was dramatically reduced after 28 days.…”
Section: 6antioxidant Enzyme Activitysupporting
confidence: 93%
See 2 more Smart Citations
“…Because of particle size of nano zinc a faster diffusion through GIT membrane has taken place to reach the cells of the intestinal lining. Our data are in agreement with those obtained by Zhao et al (2014) who stated that after 14 days, birds in the 20 and 60 nano-ZnO groups had significantly greater weight gains and better feed conversion ratios. However, the body weight of birds in the 100-nanoZnO group was dramatically reduced after 28 days.…”
Section: 6antioxidant Enzyme Activitysupporting
confidence: 93%
“…Means within the same row of different litters are significantly different at (P < 0.05). The present data are in harmony with those obtained by Sahoo et al (2016) who indicated that organic zinc at 15ppm induced better growth than inorganic and nano zinc sources at the same supplementation level but, in contrast with those obtained by Zhao et al (2014), wherein chickens fed 20 or 60 mg/kg nano-ZnO resulted increased in body weight at all the weeks until the end of the experiments of 42 days. Also, Siddhartha et al (2016) showed that nano zinc supplementation improved broiler chicks weight.…”
Section: 6antioxidant Enzyme Activitysupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in accordance with Pieper et al (2015) who found that long-term supplementation with high dietary Zn (2425 mg/kg for 28 days) triggers oxidative stress reactions in the pancreas of weaned piglets. Similarly, Zhao et al (2014) found that while 20-60 mg/kg of ZnO nanoparticles in broiler diet stimulate antioxidative functions, a higher dose (100 mg/kg) can lead to hepatocyte damage and a gradual decrease in total antioxidant capacity in liver tissue. In support of the aforementioned results, Gazaryan et al (2002) suggested that Zn 2+ can interfere with mitochondrial antioxidant production and may stimulate the production of reactive oxygen species.…”
Section: Biomarker Of Oxidative Stressmentioning
confidence: 94%
“…The permeability of N-ZnO helps to avoid the adverse gastrointestinal reactions and improve the absorption of medicine (Lucas, 2010). N-ZnO has antioxidant properties in broilers (Zhao et al, 2014). But, other researches proved that higher usage of N-ZnO can increase recurrent exposure and the risk of toxicity through ingestion, inhalation or dermal contact during use, manufacture, and disposal (Balasubramanian et al, 2010).…”
Section: Introductionmentioning
confidence: 99%